(untitled) (Ibrahim Cardiac Medical Journal, 2023)
Background & Objective: Alopecia areata (AA) is an autoimmune disorder characterized by patches ofnon-scarring alopecia affecting the scalp and body hair. Previous epidemiological studies suggest a potentialpositive association between alopecia areata (AA) and several autoimmune diseases, including autoimmunethyroid disorders. The present study was therefore undertaken to determine the association between AA andthyroid disorder. Methods: This cross-sectional case-control study was carried out in the Department of Physiology, Dhaka Medical College, Dhaka over a period of 1 year from July 2021 to June 2022. A total of 40 clinically diagnosed patients of AA (case) of both sexes with age ≥18 years were taken from the Outpatient Department of Dermatology and Venereology, Dhaka Medical College Hospital (DMCH), Dhaka. An equal number (n = 40) of age-matched (withcases) apparently healthy subjects were taken as controls for comparison. In order to assess thyroid functionstatus, five variables were measured. These were free tri-iodothyronine (FT3), free thyroxine (FT4), thyroidstimulating hormone (TSH), thyroglobulin antibody (TgAb), and thyroid peroxidase antibody (TPOAb or TmAb).Thyroid disorders were evaluated in terms of hypothyroidism, subclinical hypothyroidism, hyperthyroidism, subclinical hyperthyroidism, etc. Result: In the present study, the baseline demographic and clinical characteristics were almost similar between cases and controls. The male-to-female ratio of AA patients was 1:1. The mean age was 29.9 ± 10.5 years for thecase group and 29.9 ± 10.4 years for the control group. Most of the patients with AA had mild disease (45%)followed by moderate (42.5%) and severe (12.5%) diseases. The study demonstrated the prevalence of thyroiddys function to be significantly higher in the case group (20%) than that in the control group (5%) with a risk of developing thyroid disorder in patients with AA being 4.7(95% CI = 0.9 – 23.9) times higher than that in the control group (p = 0.043). There were significant differences between cases and controls in terms of levels of TSH,FT3 and FT4. The present study demonstrated a significant difference between cases (AA patients) and controlswith respect to thyroid auto-antibodies (Tg-Ab, TPO-Ab) as well. Tg-Ab and TPO-Ab were also found positive in 12euthyroid alopecia areata patients. Conclusion: The prevalence of thyroid disorders is comparatively high in alopecia areata patients as opposed to healthy individuals of similar age and sex. The serum levels of TSH, TPO-Ab and Tg-Ab are significantly elevated, and the levels of free T3 and free T4 are significantly dropped in patients of alopecia areata compared to theirhealthy counterparts. However, Tg-Ab and TPO-Ab may be present in euthyroid alopecia areata patients. Ibrahim Card Med J 2022;12(2):15-20